Phytoremediation, a Cheaper and Ecological Alternative in Solving Historical Soil Pollution: Array - Turtureanu, Anca; Dobrescu, Codruța Mihaela; Dorobat, Leonard Magdalin (Journal of Danubian Studies and Research, 2021)
Romania, since the pre-accession phase to the European Union, has committed itself to implementing environmental policies in accordance with European legislation. Regarding the stage reached, only a part of these obligations regarding the ecological sanitation of some post-industrial sites were respected, an insignificant part. Many places in Romania are characterized by an emanating, historical pollution. This is the result of decades of inefficient communist economy, with little respect for the environment, high energy consumption and little-added value. To continue solving these problems of historical pollution, enormous funds are needed and the ecological remediation and reconstruction works will be more numerous and increasing. An efficient, environmentally friendly and inexpensive solution is the application of bioremediation methods. These ecological methods are widely observable worldwide, especially in developed countries. Phytoremediation, in turn, is a major method of depollution of contaminated ecosystems, especially those polluted with oil residues from old petrochemical plants or heavy metals from metal mining and processing activities. These economic activities had a wide spread on the Romanian territory during the socialist epoque, and that is why today many polluted areas have remained ecologically unhealthy. Phytoremediation being a much cheaper method than others, which falls within the concept of sustainable development, has great economic and ecological potential in Romania and must be assumed as a variant that should be quickly applied to the situation on the ground. This will be even more necessary in the context in which budgetary allocations for solving environmental problems are in competition with other needs that require the same limited source of funding.